Novel thermophilic pectinases for recycling sustainable biomass - Flores Fernández, Carol Nathali (2023)
Large amounts of pectin-rich biomass are produced mainly from juice and sugar industries. Pectinases represent an economical and eco-friendly alternative to depolymerise it in comparison with chemical treatments, for both obtaining bio-based chemicals and improving industrial bioprocess. This thesis aimed to identify novel thermophilic pectinases, carry out their functional characterisation, and explore the synergistic activity between pectin methylesterases (PMEs) and exo-polygalacturonases (exo-PGs) for pectin bioconversion into galacturonic acid (GalA). Also, the work was focused on the co-expression of genes encoding a PME and exo-PG in a single host for a cost-effective pectin bioconversion into GalA. Finally, the synergistic activity between PMEs and pectate lyases (PGLs) for improving pectin depolymerisation, useful in several industrial processes, was also explored. A total of seven genes encoding thermophilic bacterial pectinases were successfully cloned, and the enzymes expressed included two exo-PGs (TMA01 and BLI04), two PMEs (BLI09 and SAM10) and three PGLs (TMA14, TFU19 and TFU20). Mn²⁺ significantly increased the exo-PGs activity (2-fold) and did not affect PMEs action allowing its inclusion in the synergistic reactions. Both exo-PGs and PMEs exhibited high activity and stability between 40 and 90 °C up to 24 h. The synergistic reactions between BLI09 PME paired either with TMA01 or BLI04 exo-PGs using apple and citrus pectin were the most successful for pectin bioconversion, releasing around 2.5 mM GalA (29% yield). GalA release by pectinases is important in industry since it is a key chemical for the synthesis of a number of valuable compounds. In addition, enzymes allow to release this compound in a sustainable biocatalytic process. Four co-expression plasmids containing a PME and exo-PG were constructed in pETDuet-1, in which the gene’s cloning order as well as the presence of a T7 terminator behind the second gene affected the pectinases expression levels. TMA01 and BLI04 exo-PGs were well expressed in all the constructs, but BLI09 PME was better expressed cloned downstream the exo-PGs in MCS-2 and with the presence of its own T7 terminator behind. Thus, the most successful co-expression plasmids were the constructs 3 and 4 (pETDuet-TMA01-BLI09 and 4 pETDuet-BLI04-BLI09, respectively) which allowed the release of around 3 mM GalA (35% yield) from apple and citrus pectin. GalA release was limited by product inhibition since this compound had an inhibitory effect on both exo-PGs from around 3 mM. Finally, the three PGLs were characterised showing Ca²⁺ dependant activity, while Mn2+ significantly improved the activity of TFU20 (2.5-fold). All the PGLs exhibited optimum activity and stability between 50 and 90 °C and Ca²⁺ improved their thermal stability. The three PGLs were able to depolymerise pectin, but the main peak of 650 kDa observed in both non-esterified and esterified substrates was depolymerised only in the non-esterified. These results evidenced the need of a synergistic action of PGLs with PMEs for improving esterified pectin depolymerisation. Thus, the smallest oligogalacturonates (oligoGalA) because of this main peak depolymerisation in apple, citrus and sugar beet pectin were obtained from synergistic reactions between SAM10 PME paired either with TMA14 (4 – 10 kDa) or TFU20 (8 – 25 kDa). Overall, this work provided optimum conditions of activity of novel thermophilic pectinases, which are fundamental to set up compatible operational conditions especially in synergistic reactions. Synergistic activity between pectinases allowed the release of GalA and co-expression systems made the pectin bioconversion process more cost-effective. Synergistic activity also improved esterified pectin depolymerisation, useful and applicable to several industries. These findings provided further insights for recycling sustainable biomass within a context of biorefineries and circular economy.